STUDY OF THE RANGE OF ANTIFUNGAL DRUGS FOR TOPICAL USE IN THE PHARMACEUTICAL MARKET OF UKRAINE - РОЇК, О. М.; КЛЮЙ, О. С.; ГОРБИК, А. Ю. (Technologies and Engineering, 2024)
The purpose. To analyse the assortment of the domestic pharmaceutical market of antifungal medicines for topical use, taking into account all forms of release Methodology. To analyse the segment of antifungal medicinal products for topical use, the data from the State Register of Medicinal Products of Ukraine, the ATC classification system of the electronic resource Compendium.online and the information search program Morion were used. The study used methods of statistical, structural and graphical analysis of antifungal medicinal products for topical use in order to further generalise and systematise the results obtained. Results. A detailed analysis of official sources of information on the status of antifungal drugs for topical use registered and authorised for medical use in Ukraine was carried out and an information dataset of 102 drug names was formed. It was found that the medicinal products under consideration are represented in one anatomical group D01A Antifungal drugs for topical use. The marketing analysis revealed that the largest number of antifungal medicinal products for topical use are those containing the following active pharmaceutical ingredients: naftifine – 22%, terbinafine – 18%, ketoconazole – 13%, clotrimazole – 11%. It is determined that 50% of the market segment under study is occupied by domestic manufacturers with their own production facilities and extensive experience in the development and production of antifungal medicines. A study of the nomenclature of antifungal medicinal products for topical use was carried out and it was found that the most common dosage forms among the entire range under consideration are soft dosage forms (creams 36%, ointments 6%, gels 7%), liquid dosage forms (solutions for external use 26%, shampoos 6%, suspension 1%) and skin sprays10%. Scientific novelty conducted a marketing analysis of the range of antifungal medicines for topical use for the period January–September 2023. Practical significance is to conduct a detailed, structured marketing analysis of antifungal medicines for topical use with the aim of further developing new medicines for the treatment of fungal lesions of the skin and appendages, as 20–25% of the world’s population suffers from mycoses of the skin, trunk, and feet, making mycoses one of the most common forms of skin infections.